KONSEP KENEGARAAN MUHAMMAD HATTA (Tinjauan Filsafat Politik) - Jalil, Mat (STAIN Jurai Siwo Metro, 2004)
The presented its title in The civil society concept of Muhammad Hatta. Based on the political philosophy. This is critically discussing the real concept of Muhammad Hatta, which is finding the systematical explanation and the coherence of the civil society concept of Muhammad Hatta as one of though the political philosophy. The main goal is to know the civilian concept of Muhammad Hatta for the political plan of our nation and our country now days. Muhammad Hatta stated that the fairness of a democratic country and guide the society without the discrimination become the basic idea in thinking and the struggle about the country, so the country is a real republic country based on the society using the decentralization and the enhance the district area.Â Keywords : The Fairness Of a Democratic Country.